Lattice evolution, ordering transformation and microwave dielectric properties of rock-salt Li3+xMg2–2xNb1-xTi2xO6 solid-solution system: A newly developed pseudo ternary phase diagram. (March 2021) - Zhang, Xing; Fang, Zixuan; Yang, Hongyu; Zhao, Peng; Zhang, Xiao; Li, Yuanpeng; Xiong, Zhe; Yang, Hongcheng; Zhang, Shuren; Tang, Bin
Abstract: New types of multi-component Li3+ x Mg2–2 x Nb1- x Ti2 x O6 (0 ≤  x  ≤ 1) solid-solution ceramics were designed based on the Li2 TiO3 −Li3 NbO4 −MgO pseudo ternary phase diagram and studied for microwave dielectric applications. As the substitution amount ( x ) increased, we detected the phase transitions among the orthorhombic, cubic, and monoclinic phase driven by the compositional changes, as well as accompanied by an order-disorder-order transformation. A full range of solid solutions was formed between the Li3 Mg2 NbO6 and Li2 TiO3 endmembers, with no trace of other impurities. In the sample with the low substitution concentration ( x  = 0.2 mol), a coherent phase interface (CPI) between the cubic and orthorhombic lattices was formed with no obvious misfit dislocation or stacking fault, indicating the small differences in crystal configuration, chemical bonding properties, and subcell lattice parameters between the two phases. Besides, there were observed diverse reconstructed superlattices, one kind is that possessed a "transition form" of the two phases and was formed nearby the CPI, and the other kind was formed based on the cubic or orthorhombic lattices independently and was observed on a larger scale nearby the CPI. The preferential substitutions of the non-equivalent cations, which were determined by ionic radius, electronegativity, and local electroneutrality, and the interfacial strains would together act on the formation of these superlattices. The Q  ×  f values measured in the microwave range increased considerably around the compositional range where the superlattices were formed, indicating that the effect of reconstructed superlattices on the intrinsic loss should not be overlooked. As proven by the dielectric response in the high-frequency range (0.5 − 1 THz), the x  = 0.2 sample indeed showed extremely higher Q  ×  f values than other ones, which illustrated that the sample with the reconstructed superlattices was related to a small lattice vibrational anharmonicity that is favorable for the low dielectric loss. Graphical abstract: Image, graphical abstract